Nematodes of Amphibians from the South American Chaco: Distribution, Host Specificity and Ecological Aspects - Gonzalez, Cynthya Elizabeth (2021)
This is the first review of the nematode parasites of amphibians from Dry Chaco (DC) and Humid Chaco (HC) ecoregions of South America, covering aspects related to their systematics, distribution, host range and ecology, including their life cycles. Of approximately 100 species of amphibians that inhabit these ecoregions, the nematode parasites of 32 species are known. The parasite species consisted of 51 taxa: 27 in HC and 18 in DC. The family Cosmocercidae alone included 18 species. Aplectana hylambatis and Cosmocerca podicipinus showed the widest geographical and host distribution. Leptodactylus bufonius and Rhinella major presented a high number of nematode parasites. The species richness of nematodes was related to the host body sizes and to the strategy to obtain prey. The mean species richness was higher in terrestrial amphibians with intermediate characteristics in the generalist–specialist spectrum in terms of diet, and in amphibians with intermediate characteristics between actively foraging and the “sit-and-wait” approach in terms of searching for prey. The patterns of similarity among amphibian species showed groups linking with their habitats. Nematodes usually have direct life cycles with the infectious form entering the host passively or actively. However, many amphibians are also involved in heteroxenous cycles that develop in the aquatic environment.